PSYCHOLOGICAL TRAINING OF WRESTLERS IN THE PROCESS OF TRAINING PREPARATION AND CONTROL - Gapparov Khafiz Zakhidovich; Akhmedov Hikmatilla Rakhmanberdievich (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, psychological training is understood as a set of psychological and pedagogical activities and conditions relevant to the activities and life of athletes. They focus on shaping the mental functions, processes, situations, and personality traits that enable wrestlers to successfully address the challenges of training and competing.